2016
DOI: 10.1007/s00394-016-1327-5
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavone intake and prevalence of depressive symptoms during pregnancy in Japan: baseline data from the Kyushu Okinawa Maternal and Child Health Study

Abstract: Our study is the first to show independent inverse relationships between intake of total soy products, tofu, tofu products, fermented soybeans, boiled soybeans, miso soup, and isoflavones and depressive symptoms during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…In this study, the diet quality score was positively associated with the intakes of specific dietary components whose higher intakes were previously suggested to lower the risk of depressive symptoms. These include dairy products ( 35 , 61 ) , fruit ( 10 , 11 ) , seaweed ( 26 ) , soya products ( 27 ) , vegetables ( 10 , 11 ) , EPA+DHA ( 6 , 7 ) , dietary fibre ( 34 ) , Ca ( 35 ) , Mg ( 36 , 37 ) , Fe ( 38 ) , folate ( 4 , 5 ) and vitamin C ( 39 ) . The score was also inversely associated with intakes of confectioneries and sugar (as a source of added sugar) ( 34 ) , soft drinks ( 62 , 63 ) and total and saturated fats ( 8 ) , and higher intakes of these foods and nutrients have been suggested to increase the risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the diet quality score was positively associated with the intakes of specific dietary components whose higher intakes were previously suggested to lower the risk of depressive symptoms. These include dairy products ( 35 , 61 ) , fruit ( 10 , 11 ) , seaweed ( 26 ) , soya products ( 27 ) , vegetables ( 10 , 11 ) , EPA+DHA ( 6 , 7 ) , dietary fibre ( 34 ) , Ca ( 35 ) , Mg ( 36 , 37 ) , Fe ( 38 ) , folate ( 4 , 5 ) and vitamin C ( 39 ) . The score was also inversely associated with intakes of confectioneries and sugar (as a source of added sugar) ( 34 ) , soft drinks ( 62 , 63 ) and total and saturated fats ( 8 ) , and higher intakes of these foods and nutrients have been suggested to increase the risk.…”
Section: Discussionmentioning
confidence: 99%
“…The diets consumed by Japanese are typically characterised by high intakes of rice, soya products, fish, seaweeds and green tea and low intakes of animal fat and soft drinks ( 25 ) . Actually, previous Japanese studies have shown inverse associations of intakes of fish ( 8 ) , seaweed ( 26 ) , soya products ( 27 ) and green tea ( 28 , 29 ) with the prevalence of depressive symptoms. To our knowledge, however, only a few studies have focused on the association between dietary patterns and depressive symptoms in Japanese ( 30 32 ) .…”
mentioning
confidence: 99%
“…Isoflavones are a vital group of phytochemicals in soybean sprouts. Consumption of soy products containing isoflavones reduces depressive symptoms during pregnancy [ 10 ]. High dietary isoflavone intake may significantly increase fertility in humans [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, In a recent paper by Miyake et al, the researchers studied the association between soy isoflavone intake and the prevalence of depressive symptoms in 1745 pregnant Japanese women [1]. They concluded that higher intake of soy products was associated with lower prevalence of depressive symptoms during pregnancy.…”
mentioning
confidence: 99%